A higher altitude enclave of humid forest in the semi-arid of Brazil holds a diversity of conidial fungi on leaf-litter - Marcela Alves Barbosa; José Fredson da Silva Alves dos Prazeres; Elaine Malosso (Acta Botânica Brasílica, 2022)
ABSTRACT Brejos de Altitude are enclaves of higher altitude humid forests in the semiarid lowlands of the North-eastern of Brazil. They present unique characteristics in terms of soil and air humidity, temperature, vegetation cover, and biodiversity. Due to these conditions, many cattle ranchers and farmers develop activities that have caused habitat loss and fragmentation of biodiversity. In this study, we aimed to describe the diversity of conidial fungi that occur in the leaf litter of the riparian vegetation in a Brejo de Altitude in Pernambuco, Brazil. Decomposing leaf material was collected from the forest floor in the dry and rainy periods of 2019, incubated in moist chambers and observed daily for fungal structures, for up to 45 days, under dissecting microscope and light microscope. Eighty-four taxa of fungi were identified, totaling 335 occurrences. The air and soil temperature, and precipitation showed an influence on the fungal community. Species richness was greater in the dry period and abundance was greater in the rainy period. The multivariate analyses revealed differences in the conidial fungi community between the dry and rainy periods. A high richness of leaf litter conidial fungal was uncovered in this area of humid forest surrounded by the semiarid vegetation of Caatinga.